PEMBUKTIAN DEBITUR TERHADAP ACTIO PAULIANA DALAM KEPAILITAN - abd jalil hamzah (Jurnal De Jure Muhammadiyah Cirebon, 2017)
If careful at section 2 UUK of when debt have fallen due and cannot be paid by debitor, creditor earn direct apply the bankrupt statement for its debitor, problems of arising out at rule section 2 UUK do not mind how much/many amount owe the debitor which can be billed for, become the creditor invoice which relative minimize its amount can apply the bankrupt statement to debitor owning valuable asset very is big compared to with the amount of creditor invoice becoming base raised by a bankrupt application. Other problem to arise here is whether/what no chance which can be passed to by a debitor to can to improve; repair the its finance circumstance until really can be expressed by that debitor unable to again pay [for] its debts is principal sehinggga from actio pauliana is not applied, visible miscellaneous in the world of banking giving time tolerance of at its debitor before credit given by classified as credit stuck the existence of this time tolerance possible can give the protection to debitor beside whether/what considered necessary by applying of cancellation of contract of debitor with the other party which not yet of course conducive to the loss for its creditor is this matter require to be proved. Herein after for company debitor getting the time tolerance expected can make healthy to return his company until return in a state of able to pay for its debts accompanied on that condition. Keyword : Evidence, Actio Pauliana, Bankrupt